Optimised design of concrete recycling networks: The case of North Rhine-Westphalia. (November 2021) - Tsydenova, Nina; Becker, Tristan; Walther, Grit
Highlights: Construction and demolition waste is either landfilled or used for roadworks. Recycled concrete aggregates can be reused for the construction of new buildings. Optimisation model minimises the total costs and the mining of natural aggregates. Concrete with recycled aggregates is viable without natural aggregates supply. Minimum quota of recycled concrete allows to strengthen closed loop material cycle. Abstract: In Germany, construction and demolition waste is either landfilled or used for roadworks after being treated in recycling plants. However, recycled concrete aggregates from building demolition can be reused for the construction of new buildings, which allows to close the material loop of concrete. The aim of this study is to develop a decision support system (DSS) in order to investigate the economic impacts and consequences of recycling concrete from building demolition in a closed loop material cycle. To do so, we propose a bi-objective mixed-integer linear optimisation model that provides information on the number and location of installed sorting screens and defines the material flows within a comprehensive regional recycling network covering all processes from building demolition to construction of new buildings. While the economic objective function minimises the total costs of the recycling network, the circularity objective function minimises the amount of primary natural aggregates required for concrete manufacturing. We apply our optimisation model to the German federal state of North Rhine-Westphalia. Results show that under current conditions the manufacturing of concrete with recycled concrete aggregates is economically viable predominantly in areas without local supplies of natural aggregates. In addition, analysis of the trade-offs between the two objectives as well as recommendations on the design of political regulations and economic instruments to foster such recycling networks are presented.